'Only work and sleep': seafarers' perceptions of job demands of short sea cargo shipping lines and their effects on work and life on board. Issue 7 (3rd October 2017) - Pauksztat, Birgit
ABSTRACT: Previous research on job demands in seafaring has focused on the effects of workload and circadian disturbance on seafarers' health and fatigue. Taking a more comprehensive approach, this study identifies job demands of short sea cargo shipping lines and explores their effects on work and life on board. Data came from 54 interviews with officers and crew on five cargo ships. Findings revealed job demands related to characteristics of the schedule, ports, and sea voyages; these were not only associated with workload and circadian disturbance, but also with the difficulty of the work, the ability to plan ahead, and intrusions from third parties. Job demands affected outcomes through two interconnected processes. First, job demands had direct and indirect effects on fatigue and the working climate on board. Second, potential positive effects of job demands (i.e. interesting work and pay) were related to motivation and, together with a good working climate, could reduce turnover. Connecting the two processes, a good working climate was pivotal in counteracting negative emotions and supporting motivation and collaboration. In this way, it functioned as a key resource. External constraints could either buffer or reinforce these effects.